2006
DOI: 10.1063/1.2352742
|View full text |Cite
|
Sign up to set email alerts
|

Mode- and bond-selective reaction of Cl(P3∕22) with CH3D: C–H stretch overtone excitation near 6000cm−1

Abstract: Experiments explore the influence of different C-H stretching eigenstates of CH3D on the reaction of CH3D with Cl(2P3/2). We prepare the mid |110>|0>(A1,E), mid |200>|>0(E), and mid |100>|0> +nu3 +nu5 eigenstates by direct midinfrared absorption near 6000 cm(-1). The vibrationally excited molecules react with photolytic Cl atoms, and we monitor the vibrational states of the CH2D or CH3 radical products by 2+1 resonance enhanced multiphoton ionization. Initial excitation of the |200>|0>(E) state leads to a twof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 38 publications
1
53
0
1
Order By: Relevance
“…Lower panel: single-site RPH dissociation probabilities for CH 4 initially excited to antisymmetric stretch (1 0 (red) and 1 00 (brown)) and symmetric stretch (3 0 (blue)) states on Ni (100) View Article Online methane and atomic reactants such as H and Cl in the gas phase, 187 where mode specific and bond selective chemistry is well established. [188][189][190][191][192][193][194][195][196] Finally, we note in passing that Harrison and coworkers have advanced a statistical approach to methane DC processes. [197][198][199] While reproducing many observed properties, the statistical models are fundamentally incompatible with the mode specific dynamics supported by the overwhelming experimental and theoretical evidence.…”
Section: B Chmentioning
confidence: 96%
“…Lower panel: single-site RPH dissociation probabilities for CH 4 initially excited to antisymmetric stretch (1 0 (red) and 1 00 (brown)) and symmetric stretch (3 0 (blue)) states on Ni (100) View Article Online methane and atomic reactants such as H and Cl in the gas phase, 187 where mode specific and bond selective chemistry is well established. [188][189][190][191][192][193][194][195][196] Finally, we note in passing that Harrison and coworkers have advanced a statistical approach to methane DC processes. [197][198][199] While reproducing many observed properties, the statistical models are fundamentally incompatible with the mode specific dynamics supported by the overwhelming experimental and theoretical evidence.…”
Section: B Chmentioning
confidence: 96%
“…[21][22][23][24][25][26][27][28][29][30][31][32] The experimental measurements and dynamical calculations for H-atom abstraction reactions involving simple alkanes illustrate a wealth of dynamical behaviour. For example, the shape of the transition state, with near linear Cl-H-C moiety, is reflected in the low rotational excitation of HCl products; scattering angles are largely determined by impact parameter and their distributions can vary with product rotational and vibrational quantum states; 1 and the reactions of Cl atoms with methane and partially deuterated isotopologues exhibit reagent vibrational mode specificity, [4][5][6][7][9][10][11][12]14,15,[33][34][35][36][37][38][39][40] electronically non-adiabatic pathways, 29,31,41,42 and evidence for scattering resonances. 43 Reactions of functionalized organic molecules (RH = alcohols, 24,44,45 amines, 46 alkyl halides 23,47 and linear and cyclic ethers 24,44,…”
Section: Introductionmentioning
confidence: 99%
“…The reverse reaction of Cl atoms with CH 4 ͑and isotopologs resulting from partial or complete deuteration͒ is well established as a benchmark polyatomic reactive system for studying scattering and vibrational mode and bond specific dynamics. [15][16][17][18][19][20][21][22][23][24] Reaction of Cl * with CH 4 adiabatically correlates with an electronically excited state of the CH 3 radical, and nonadiabatic formation of the energetically accessible CH 3 ͑X 2 A 2 Љ͒ + HCl products is not observed for collisions with energies just above the energetic barrier 25,26 but does occur at much higher collision energies. 27 In studies of the kinetics of collisional processes between Cl * atoms and small hydrocarbons, Matsumi et al 28 demonstrated that the rate of SO quenching of Cl * to grounda͒ Present address: Solar-Terrestrial Environment Laboratory, Nagoya University, Nagoya 464-8601, Japan.…”
Section: Introductionmentioning
confidence: 99%